2013
DOI: 10.1371/journal.pone.0068622
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Laryngeal Carcinomas from Precursor Lesions by Diffusion-Weighted Magnetic Resonance Imaging at 3.0 T: A Preliminary Study

Abstract: BackgroundDiffusion-weighted magnetic resonance imaging (DWI) has been introduced in head and neck cancers. Due to limitations in the performance of laryngeal DWI, including the complex anatomical structure of the larynx leading to susceptibility effects, the value of DWI in differentiating benign from malignant laryngeal lesions has largely been ignored. We assessed whether a threshold for the apparent diffusion coefficient (ADC) was useful in differentiating preoperative laryngeal carcinomas from precursor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…An MRI scan improves differentiation between inflammatory reaction, tumor, and liquid retention. The combination of DWI and ADC may differentiate malignant tumors from precancerous lesions and benign tumors [18]. In the present study, the T1-weighted signals and the T2-weighted signals were hyperintense.…”
Section: Resultssupporting
confidence: 48%
“…An MRI scan improves differentiation between inflammatory reaction, tumor, and liquid retention. The combination of DWI and ADC may differentiate malignant tumors from precancerous lesions and benign tumors [18]. In the present study, the T1-weighted signals and the T2-weighted signals were hyperintense.…”
Section: Resultssupporting
confidence: 48%
“…This study did not meet our inclusion criteria, because it only involved patients with premalignant lesions. Correspondingly, Shang et al reported superior accuracy of diffusion‐weighted magnetic resonance imaging compared to VS (96% vs. 76%, respectively) in differentiating laryngeal cancer from precursor lesions, but missing details concerning VS findings and histopathological evaluation prevented inclusion in the present study. Furthermore, patients with nonglottic laryngeal cancers were included in the study population, and those were impossible to exclude from the reported data.…”
Section: Discussionmentioning
confidence: 84%
“…For years, VS has been recommended for assessing vocal cord lesions, especially when invasive lesions are suspected . However, the value of VS in predicting the degree of dysplasia or malignant invasion has recently been questioned . Colden et al described a normal VS evaluation in only two of 28 vocal cord lesions with not more than intraepithelial atypia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No other articles were excluded based on language. Eventually, 10 studies were eligible for critical appraisal. Cross‐reference checking of these studies on PubMed and Scopus did not reveal any relevant studies.…”
Section: Resultsmentioning
confidence: 99%